Perancangan Sistem Informasi Absensi Siswa Berbasis Android Menggunakan Metode Waterfall - Ahmad Fatih; Ilham Aditya Chandra (Journal of Informatics Management and Information Technology, 2025)
Student attendance is a crucial component of school administration, directly linked to discipline and attendance evaluation. At MA Nurul Falah, attendance recording is still conducted manually, which takes approximately ±10 minutes per class. This method is not only time-consuming but also prone to recording errors, negligence, and data loss. These issues can affect the accuracy of attendance data, which in turn impacts academic assessment and student discipline evaluation. This study aims to design and develop an Android-based student attendance information system that enhances the efficiency and accuracy of attendance recording. The research employs a Research and Development (R&D) approach using the Waterfall development model, which is suitable for building systems in a structured and systematic manner. The application is developed using Java and PHP programming languages, with MySQL as the database and Android Studio as the development environment. System testing is carried out using the BlackBox method to ensure all functionalities work as expected, along with a usability evaluation using the System Usability Scale (SUS) to measure user satisfaction and ease of use. The testing results show that the application reduces attendance recording time to approximately ±2 minutes per class (an efficiency improvement of around 80%), with a 100% success rate in functionality across various Android devices. This system offers a digital solution that is effective, efficient, and modern for managing student attendance. It is expected that the system can be further adopted and expanded by other educational institutions as a reference in implementing digital-based administrative processes in schools.